Woman cooking at fire - Lev Grigorevich Brodaty:::Creator::::::::::::
Glava Dvadtsat Pervaya' (Chapter 21). Woman cooking at a fire, a man and car in background and a child lying next to a woman. Pen and ink lithograph. Lev Grigorevich Brodaty was born in Warsaw in 1889. A graphic artist, poster artist and illustrator, he created these for a Russian translation (possibly the first) of The Grapes of Wrath. He died in Moscow in 1954.